(untitled) (Malaysian Journal of Civil Engineering, 2017)
The understanding of environmental influenced on the properties of polymer mortar composites is still far from complete. This preliminary investigation is to provide some informative data to this unsettle topic. When cured in hot humid environment, it has been observed that the specified compressive strength is obtained as early as 1 day age but the modulus of elasticity is significantly less than the specified values. The flexural strength of polymer mortar composites has been expressed as a function of compressive strength. However, the compressive strength of polymer mortar composites cannot be used as a measure of the modulus of elasticity.